Autocratic Fatherhood, Violent Sexuality, and Critique in Mark Behr's The Smell of Apples. Issue 1 (2nd January 2022) - Nabutanyi, Edgar
Abstract : The recurrence of the theme of sexual violence in recent South African fiction has elevated sexual violence to a symbol of apartheid's legacy of patriarchy. Although texts that feature sexual violence are often analysed as allegories of the legacy of apartheid's patriarchal control and racial domination, I argue that texts like Mark Behr's The Smell of Apples de-allegorise and/or de-politicise sexual violence. Rather than read The Smell of Apples as an exculpatory narrative of white South Africa's complicity in apartheid's atrocities, I argue that Behr's depiction of sexual violence in a space where the child is supposed to be safe and by a perpetrator who is known to the victim and from whom the victim expects protection complicates the South African rape narrative. Thus, I contend that Behr crafts an ingenious and nuanced register for his witness-protagonist to subvert the muzzling power of the rapist-father to disclose the horror of sexual abuse for both victim and witness.